A Study on the Potential of Cinnamon and Jasmine as an Alternative Therapy for Managing Respiratory Tract Infections - Muhammad Ainur Rosyid Ridho; Ratri Dwi Indriani (Journal of Medicine and Health Technology, 2025)
Respiratory tract infections (RTIs) remain a significant global health burden, particularly due to increasing antibiotic resistance. Natural compounds have gained interest as alternative therapies to address this challenge. This study explores the potential of cinnamon (Cinnamomum sp.) and jasmine (Jasminum sp.) as herbal remedies for RTI management. Cinnamon contains bioactive compounds such as cinnamaldehyde and eugenol, which exhibit antibacterial, anti-inflammatory, and antioxidant properties. Jasmine, on the other hand, possesses linalool and benzyl acetate, which contribute to its bronchodilatory, anti-inflammatory, and antimicrobial effects. The synergistic interaction between these two botanicals may enhance immune response, reduce airway inflammation, and inhibit respiratory pathogens. This systematic review compiles evidence from in vitro, in vivo, and clinical studies to evaluate the efficacy of cinnamon and jasmine in RTI treatment. The findings suggest that both plants hold promise as complementary or alternative therapies, potentially reducing reliance on conventional antibiotics and mitigating antimicrobial resistance. Further clinical trials are recommended to confirm their therapeutic applications.